Power Generation and Storage by Piezoelectric Cells - Madhusudan Ghimire; Pasang Temba Sherpa; Dipendra Karki; Binod Bhandari (KEC Journal of Science and Engineering, 2025)
Energy consumption is an indicator of development of the universe. Modern world needs a huge amount of electrical power to meet up the current energy demand whereas the resources of conventional energy sources are diminishing steadily in response of vast consumption of energy. So, alternate sources of energy are required to fill up the large gap between demand and supply. This paper covers the production of energy through piezoelectric effect in which certain materials have the ability to build up electricity from having pressure or strain applied to them; this can be achieved through a design of piezoelectric tile/s. When people walk, their energy gets wasted, by using piezo electric transducers (PZT) like Lead Zirconium Titanate, we can convert this wasted energy produced by the pressure of moving people into electrical energy which can be used for different purposes such as auto street lighting, emergency lighting in commercial buildings, etc.